Utilization of colorectal cancer screening tests across European countries: a cross-sectional analysis of the European health interview survey 2018-2020 - Ola, Idris; Cardoso, Rafael; Hoffmeister, Michael; Brenner, Hermann (The lancet. Regional health, 2024)
Background - Colorectal cancer (CRC) screening has been shown to reduce CRC incidence and mortality, and most European countries have started to implement CRC screening programs in the past 20 years. Consequently, this study aimed to estimate the utilization of fecal tests and colonoscopy, as well as investigate factors associated with their utilization based on specific screening program characteristics in European countries. - Methods - We analyzed data from the European Health Interview Survey 2018-2020 to determine the utilization of fecal tests [guaiac-based fecal occult blood test (gFOBT) or fecal immunochemical test (FIT)] within the preceding 2 years or colonoscopy within the preceding 10 years among people aged 50-74 years, based on the type of screening offered in each country. Using multivariable logistic regression and sub-group meta-analysis, factors associated with screening use were determined. - Findings - The analyses included data from 129,750 respondents across 29 European countries, with participant counts ranging from 1511 individuals in Iceland to 11,755 individuals in Germany. Unit response rates ranged from 22% to 88%. The use of either test was highest among countries with fully rolled-out programs with fecal tests [from 37.7% (867/2379) in Croatia to 74.9% (2321/3085) in Denmark] and in countries offering colonoscopy as an alternative screening method [from 26.2% (854/3329) in Greece to 75.4% (1192/1760) in Luxembourg]. We observed the lowest utilization of either test in countries with no program or small-scale programs [6.3% (195/3179) in Bulgaria to 34.2% (722/2144) in Latvia]. Across all types of screening offers, younger age, being without a partner, low education, rural residence, and living in large households were associated with lower utilization, as were poor lifestyle scores and prolonged periods without physician consultation. - Interpretation - Our findings point to large disparities and much room for improvement in CRC screening offers and utilization across Europe. - Funding - There was no funding source for this study.
Gesehen am 08.01.2025